2016
DOI: 10.1155/2016/9406758
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Protects from Raddeanin A‐Induced Apoptosis in SGC‐7901 Human Gastric Cancer Cells

Abstract: Raddeanin A (RA) is an extractive from Anemone raddeana Regel, a traditional Chinese medicine. The aim of this study is to assess the efficacy of RA against human gastric cancer (GC) cells (SGC-7901) and explore its mechanism. MTT assay showed that RA inhibition of proliferation of SGC-7901 cells increased in a dose-dependent manner. Flow cytometry analysis and Hoechst 33258 staining showed that RA induced apoptosis on SGC-7901 cells. Meanwhile, it induced autophagy. Western blotting analysis showed that the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
(25 reference statements)
1
24
0
Order By: Relevance
“…Baik et al reported that cordycepin induced apoptosis through an extrinsic pathway and the activation of p38 MAPK in U87 cells [48]. Teng et al demonstrated that p38 MAPK is activated during RA-induced apoptosis in the human gastric cancer SGC-7901 cell line [49]. Herein, massive ROS production induced by RA was observed in GBM cells using a DCFH-DA fluorescent probe.…”
Section: Figurementioning
confidence: 94%
“…Baik et al reported that cordycepin induced apoptosis through an extrinsic pathway and the activation of p38 MAPK in U87 cells [48]. Teng et al demonstrated that p38 MAPK is activated during RA-induced apoptosis in the human gastric cancer SGC-7901 cell line [49]. Herein, massive ROS production induced by RA was observed in GBM cells using a DCFH-DA fluorescent probe.…”
Section: Figurementioning
confidence: 94%
“…A study reported that the modification at C-28 through esterification can lead to the reduction of cytotoxic potential, thus further confirming the role of this carbon moiety in the biological activities A study reported that the modification at C-28 through esterification can lead to the reduction of cytotoxic potential, thus further confirming the role of this carbon moiety in the biological activities reported for RA [31]. Various studies has shown that RA possesses cytotoxic potential through inhibition of proliferation, invasion and induction of apoptosis in multiple human carcinogenic cells including breast cancer, hepatocellular carcinoma, gastric cancer, and non-small cell lung carcinoma cells [35][36][37][38]. In addition, RA has also shown inhibitory properties at low concentrations against histone deacetylases (HDACs), further suggesting its cytotoxicity against cancer cells [31].…”
Section: Introductionmentioning
confidence: 76%
“…Molecules 2020 , 25, 1035 3 of 21 reported for RA [31]. Various studies has shown that RA possesses cytotoxic potential through inhibition of proliferation, invasion and induction of apoptosis in multiple human carcinogenic cells including breast cancer, hepatocellular carcinoma, gastric cancer, and non-small cell lung carcinoma cells [35][36][37][38]. In addition, RA has also shown inhibitory properties at low concentrations against histone deacetylases (HDACs), further suggesting its cytotoxicity against cancer cells [31].…”
Section: Molecular Targets Of Ramentioning
confidence: 99%
“…Autophagy maintains a homeostatic balance via protein degradation and the turnover of destroyed cellular organelles [48]. Autophagy was not induced with midazolam as midazolam cytotoxicity was not reduced by pretreatment with autophagy inhibitors (3-methyladenine and bafilomycin A1) in the OSCC cell lines [30].…”
Section: Resultsmentioning
confidence: 99%